Aplikasi Ujian Berbasis Komputer Pada MTs NW Lenek 1 - Yunita Astuti; Lalu Puji Indra Kharisma; Ahmad Ashril Rizal (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2020)
In the current era of globalization, information technology is developing very rapidly, both in terms of infrastructure, networks, devices and software. This encourages digitalization in all aspects of life, including the implementation of examinations at various educational institutions. Exams as a way to evaluate the learning process to measure the level of achievement of the abilities, personality and intelligence of students. So that making exams is an important stage in the teaching and learning process. Several years ago, the implementation of exams in various schools in Indonesia still used the manual method, namely using question and answer papers. Examination in this way presents a variety of very complex problems, starting from the level of cheating and the problems in distributing questions to various regions. For this reason, the government began launching the National Examination and Computer-based School Examination to overcome these obstacles. Including MTS NW Lenek 1, which has implemented the Computer-Based National Examination (UNBK). For this reason, the authors developed an exam application at MTS NW Grandma 1, to provide convenience in the implementation and processing of exam data for students and teachers. This test application was created using the PHP programming language and MySQL database software. Keywords : Computer based exam application, MySQL